THE IMPLEMENTATION OF PROBLEM-BASED LEARNING THROUGH LESSON STUDY TO IMPROVE THE INFORMATION LITERACY OF STUDENTS IN THE ERA 21ST CENTURY LEARNING - Nanda Bhekti Fadilla; Aulya Nanda Prafitasari; Retnoningsih Indrawati (Program Studi Pendidikan IPA FKIP Universitas Jember, 2023)
Lesson Study is a model for developing the teaching profession through collaborative assessment which consists of 3 stages, namely plan, do, and see. Information literacy is an important skill for dealing with 21st century life. Information literacy determines one's success in terms of finding, selecting sources, evaluating, and using the information obtained effectively. The research objective was to determine the effectiveness of the Problem Based Learning model on information literacy through Lesson Study in biology subjects. The research subjects were 34 students of 10 grade at SMAN 1 Kencong, Jember. The research was conducted in March-May 2023. Data was collected using an information literacy test that adapted indicators from the Association of American Colleges and Universities (AACU) (2017). The data analysis technique used is descriptive quantitative. The results showed that the mean information literacy of students increased from cycle 1 (65.20%) and cycle 3 (82.60%). Increasing information literacy is accommodated by each step of the Problem Based Learning model which can support student information literacy. For this reason, the Problem Based Learning model which is taught through Lesson Study can improve students' information literacy.